Síntese e avaliação antineoplásica de novos análogos acíclicos e cíclicos da Metformina obtidos a partir de reações multicomponentes - Lima, Enia Viana Vieira (2015)
Cancer is one of the diseases that cause fear in society because it has become a stigma of death and pain. In a survey conducted by the World Health Organization (WHO), statistically, cancer is the second cause of death in the world with 13%, killing about 6.0 million people a year. It is believed that cancer in 2015 is responsible for 9 million deaths worldwide. Advances investigated in recent decades in the field of cancer chemotherapy, have admirably facilitated the implementation of other types of cancer treatment and allowed more cures. However, many cancers are intrinsically resistant to chemotherapy, while others initially respond to treatment, but become resistant to drugs. Multiple drug resistance (MDR), the most severe condition, comes when in vitro cell cultures and in vivo show simultaneous resistance to different drugs. Thus, despite the large number of compounds that make up the chemotherapeutic arsenal to fight cancer, the resistance problem requires constant search for new effective drugs to combat cancer. Thus, continuing the constant search for new compounds with activity antineoplastic prototypes being developed in our laboratory, this project aims to interdisciplinary synthesis of new acyclic and cyclic analogues of metformin with potential anticancer activity to act by cellular pathways multiple in order to avoid the acquisition of chemoresistant phenotype by tumor cells. These compounds were rationally designed by molecular docking previous studies to work in the ERK proteins, PI3K, AMPK, BRAF and ATP depletion by the inhibition of complex I of the respiratory chain, which are important targets for inhibiting cell proliferation of tumor cells. In this work were synthesized fifteen adducts of Mannich with yields ranging 51-85% oxygen-containing groups, nitrogen and sulfur. Then, some reactions were performed in order to synthesize diidropirimidinona (DHPM), cyclic analog of metformin, in order to assess the correlation between these compounds and conformational restrictions antineoplastic activity, however, no success has been obtained in this reaction. The fifteen synthesized Mannich adducts were evaluated citotoxidades in their lineages câncerhumanode lung (A549 and H460), breast (MDA-MB-231 and MCF-7) and ovarian cancer (A2780 and ES2). It is also made docking studies of these compounds with therapeutic targets PI3K, ERK2, and BRAF AMPK.